On the Analysis of Texts or Performances in Playwriting Workshops: a brief reflection on a long odyssey - Pavis (Honorary fellow, University of London ‒ London, United Kingdom), Patrice (Revista Brasileira de Estudos da Presença, 2022)
The analysis of playwriting texts and staging has passed through several evolutions between 1976 and 2016. The renewal of directing itself, as well as playwriting and performing workshops, was even more remarkable. Having, volens nolens, followed the movement of this tumultuous pedagogy in the era of impoverishment and commodification of the university, the author reports his experiences in various contexts (Paris, Canterbury, Havana, Seul, Taipei).